Pengembangan Media Komik (Nyak Ceghdas) Berbasis Budaya Lokal dengan Model ADDIE untuk Meningkatkan Kematangan Karir Siswa SMK - Telogowiyah, Diah; Febriyani, Tika; Thahir, Andi (Universitas Palangka Raya, 2025)
This study aims to develop a locally-based educational comic media Nyak Ceghdas to improve vocational students’ career maturity. The research utilized the Research and Development (RnD) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The media was validated by material, media, and language experts. Effectiveness testing involved student response questionnaires and the Wilcoxon test. Validation results indicated that the media is highly feasible, with scores from media experts (93%), material experts (90%), and language experts (87%). Student responses were positive with an average rating of 92% in small groups and 91% in large groups. Teacher responses also showed high approval at 89%. The Wilcoxon test revealed an Asymp. Sig. value of 0.000 (<0.05), indicating a significant effect of the comic media on improving students' understanding of career maturity. Therefore, Nyak Ceghdas is considered appropriate as an alternative culturally responsive career guidance media.